(untitled) (Fountain Journal of Natural and Applied Sciences, 2020)
The interaction of selected biometals with dinitrogen donor ligand, 1,10-phennathroline (phen) and amino acid, 2-amino-4-(methylthio)butanoic acid (methionine; met) resulted in isolation of three mononuclear complexes. The prepared complexes were characterized by diverse techniques including elemental and spectroscopic analysis. From the analytical and spectral data, octahedral geometry was proposed to the synthesized metal (II) complexes. Bonding of the metal ion through N- and O- donor atoms of the ligands is revealed by infrared studies. The compounds showed moderate solubility in distilled water and in some common organic solvents. In vivo evaluation of the antimicrobial activities of the metal complexes showed improved inhibitory activity against some micro-organisms as compared to the ligands, with Co(II) and Cu(II) complexes showing the highest activities against the fungi. Keywords: antimicrobial; mixed ligands; amino acid; polypyridyl